2011
DOI: 10.1002/bdm.690
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of risky decision making for potential gains and losses from ages 5 to 85

Abstract: The ability to make advantageous decisions in the face of uncertainty is an essential human skill, yet the development of such abilities over the lifespan is still not well understood. In the current study, from childhood through older adulthood, we tracked the developmental trajectory of risk taking for gains and losses, and expected value (EV) sensitivity in risky choices. In the gain domain, risk-taking decreased consistently across the lifespan. In the loss domain, risk-taking was relatively constant acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
169
5
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(198 citation statements)
references
References 76 publications
23
169
5
1
Order By: Relevance
“…Instead their decisions were influenced by the relative difference between two probabilities (PR) and not by the fact that one of the probabilities was 1.0 and therefore completely safe (figure 2). By contrast, human adults have a strong preference for options that offer a safe reward compared with any other option, provided the maximum outcome is the same [13,14]. In a sense, the chimpanzees tested here seemed to be strictly guided by (intuitive) mathematics-'How much do the two likelihoods differ?…”
Section: Discussionmentioning
confidence: 82%
“…Instead their decisions were influenced by the relative difference between two probabilities (PR) and not by the fact that one of the probabilities was 1.0 and therefore completely safe (figure 2). By contrast, human adults have a strong preference for options that offer a safe reward compared with any other option, provided the maximum outcome is the same [13,14]. In a sense, the chimpanzees tested here seemed to be strictly guided by (intuitive) mathematics-'How much do the two likelihoods differ?…”
Section: Discussionmentioning
confidence: 82%
“…Results show that younger and older adults' willingness to take a risk did not differ in the loss trials. Yet, older adults were less willing to take a risk in the gain trials [Weller et al, 2010]. Older adults, then, may be less willing to accept a potential loss (not winning) when they can prevent it.…”
mentioning
confidence: 99%
“…In a study on risky decision making employing the cups task [Levin & Hart, 2003], Weller, Levin and Denburg [2010] showed that age-related differences in risky decision making occurred depending on whether the expected outcome constituted a gain or a loss. In the cups task, there are distinct trials in which the participants can either achieve small monetary gains or avoid small monetary losses.…”
mentioning
confidence: 99%
“…While under PT it is modeled as an inflection of the value curve around the reference point, more behavioral approaches to LA have advocated that it should be defined by reference to expected value, allowing for the contribution of probabilities (e.g., Brooks & Zank, 2005). Reported differences between the developmental profile of risk taking for gains and for losses (decreasing for gains, relatively constant for losses) have been credited to the impact of LA (Weller, Levin, & Denburg, 2011). However, conditions for measuring LA are as stringent as those for measuring scope insensitivity, requiring that gains and losses be measured on a scale with a known zero (Viegas, Oliveira, Garriga-Trillo, & Grieco, 2012).…”
Section: Palabras Clavementioning
confidence: 99%